Synthesis and Characterization of Carboxymethyl Cellulose from Cellulose of Empty Fruit Bunches (EFB) - Permana, Dian; Ivana Kedang, Yohana; Naimnule, Lusia; Magdalena, Maria; Presson, Jefry (Jurnal Kimia Riset, 2025)
Empty fruit bunches (EFB), a substantial agricultural waste, offer great potential for value. This study aimed to use cellulose of EFB as a source of carboxymethyl cellulose (CMC) is considerable because cellulose-based waste is categorized as the most abundant waste in nature and is easy to obtain. Cellulose was then converted to the CMC process in several steps, including cellulose alkalization, and carboxymethylation. The resulting CMC was characterized to determine its degree of substitution, viscosity, and other physicochemical properties. Characterization with Fourier Transform Infrared Spectroscopy (FTIR) verified the effect of NaOH concentration on this property. The highest degree of substitution (DS=1.34) was observed in 50 % NaOH of carboxymethylation. Cellulose can be correctly extracted from EFB and converted to CMC. Based on the cellulose of the EFB characteristic, the proper amount of NaOH was found to get a high DS. CMC has considerable features for application on biodegradable polymer materials.